Impact of Food Origin Lactiplantibacillus plantarum Strains on the Human Intestinal Microbiota in an in vitro System - Garcia-Gonzalez, Natalia; Comas, Joan Colom; Harris, Hugh M. B.; Strain, Conall; Stanton, Catherine; Hill, Colin; Corsetti, Aldo; Gahan, Cormac G. M. (Frontiers in Microbiology, 2022)
Although the pathology of inflammatory bowel disease (IBD) is still unclear, many studies suggest a role for altered gut microbiota. In the current study we evaluated the potential impact of food-dominant Lactiplantibacillus (Lpb.) plantarum strains as a strategy to manipulate microbial diversity in complex microbiota’s derived from a healthy human and an IBD patient using a continuous fecal fermentation model. Our results showed that introduction of Lpb. plantarum strains into the community led to a significant increase in alpha diversity and a separation of control and treatment groups in beta diversity for the IBD sample. This was reflected in significant alterations in abundance of the unclassified genera, dominated by Enterobacteriaceae_unclass and Ruminococcaceae_unclass. However, the microbiota of the healthy individual was relatively unaffected following introduction of Lpb. plantarum strains. Overall, the work describes a novel application of the fecal fermentation model for the analysis of probiotic/food interactions in a disease state.